Perancangan Buku Resep Masakan dan Jajanan Tradisional Khas Tana’ Taliang - Rizkillah Lestiannina; Sunardy Kasim (Jurnal SASAK : Desain Visual dan Komunikasi, 2020)
Taliwang is the city center of a new district, West Sumbawa district, which is on the island of Sumbawa in the West Nusa Tenggra (NTB) province. West Sumbawa is one of the tourist destinations in the NTB province, apart from having beautiful tourist objects, West Sumbawa also has a wide variety of traditional food destinations. Palopo is one of the unique specialties whose basic processing process uses buffalo milk is one of the uniqueness of traditional snacks typical of Taliwang, West Sumbawa. To introduce these traditional Taliwang snacks, especially for the younger generation, a cookbook was designed with qualitative methods and a design thinking approach to get the right problem-solving solutions in designing works, by conducting observations and semi-structured interviews. The results of this study used two media, namely media. primary cookbook and traditional snacks and secondary media namely xbanner and merchandise. By designing this illustration book, it is hoped that it can attract the interest of the younger generation to want to learn about and preserve the traditional dishes and snacks of the region.